(untitled) (REMUNOM, 2026)
The objective was to longitudinally assess the quality of life of Brazilian women who experienced the pregnancy-puerperal cycle. This is a quantitative pre- and post-test study, developed in the setting of primary care in Brazilian health. Adult women who experienced na interventional proposal for groups of pregnant women in prenatal care participated. The instrument used for data collection was the World Health Organization Quality of Life (WHOQOL-bref), applied before, immediately after the conclusion of the intervention, and one year later. Descriptive statistical analysis and the Friedman Test were used. The statistically relevant results were in the physical (p value = 0.003) and environmental (p value = 0.007) domains. The actions of the pregnant women’s groups proved promising for improvement, especially in the environmental domain, as the opportunities women had to acquire new information and skills and to reframe possible heteronomous behaviors generated significant longitudinal impacts. Based on the quality of life analysis tools incorporated into interventional actions in the pregnancy and postpartum cycle, the possibilities for contemplating the real needs of women’s lives and health are expanded, indicating operational paths for health practice that are more compatible with an expanded and multiprofessional clinic.